2005
DOI: 10.1038/sj.ejcn.1602360
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lifestyle and total homocysteine in relation to MTHFR(C677T) genotype: the Inter99 study

Abstract: Background: Reduction in total homocysteine (tHcy) may be clinically relevant in the prevention of cardiovascular disease (CVD) in the general population. Objective: To examine the effects of changes in various lifestyle habits and lifestyle related biological CVD risk markers on changes in tHcy in relation to MTHFR(C677T) genotype. Design: A 1 year follow-up study. Setting: Copenhagen County, Denmark. Subjects: Statistical analyses were based on a population-based sample of 915 men and women aged 30-60 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
(71 reference statements)
1
7
0
Order By: Relevance
“…The observed associations between changes in tHcy and changes in biological risk factors are in agreement with several cross-sectional studies (Nygard et al, 1995;de Bree et al, 2001a) and confirm our previous findings of a relationship between changes in tHcy and changes in blood pressure and the lipid profile reported after 1 year of followup (Husemoen et al, 2006). The inverse relationship between weight reduction and changes in tHcy observed after 1 year was not confirmed.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The observed associations between changes in tHcy and changes in biological risk factors are in agreement with several cross-sectional studies (Nygard et al, 1995;de Bree et al, 2001a) and confirm our previous findings of a relationship between changes in tHcy and changes in blood pressure and the lipid profile reported after 1 year of followup (Husemoen et al, 2006). The inverse relationship between weight reduction and changes in tHcy observed after 1 year was not confirmed.…”
Section: Discussionsupporting
confidence: 80%
“…Changes in smoking habits between baseline and follow-up were defined into the following five categories: (1) unchanged non-smoking, (2) unchanged occasional smoking, (3) unchanged smoking, (4) stopped smoking and (5) started smoking between the two examinations. Serum cotinine measurements were used to validate the self-reported smoking cessation as described previously (Husemoen et al, 2006). A total of 20 participants (12.1%) reporting smoking cessation did not meet the validation criteria.…”
Section: Smokingmentioning
confidence: 99%
See 1 more Smart Citation
“…20,[22][23][24] However, findings are different when analyzed prospectively. 49,50 Duncan et al 50 found that 6 months of exercise increased homocysteine levels in sedentary adults, whereas Randeva et al 51 showed that 6 months of sustained brisk walking for 20 to 60 minutes 3 days a week significantly decreased homocysteine levels and increased CVF in young overweight and obese women with polycystic ovary syndrome, a group at increased risk of premature atherosclerosis. Similarly, a weight-reduction program that included physical activity had a positive effect on the homocysteine levels in obese children.…”
Section: Commentmentioning
confidence: 99%
“…Elevated plasma total Hcy concentration is an independent risk factor for coronary ischemic diseases, a stroke, vascular diseases and venous thrombosis (Husemoen et al, 2006; Mennen et al, 2002; Rasmussen et al, 2000). Life factors that were found to affect Hcy levels include age, sex, diet, plasma folate, vitamin B6, vitamin B12, smoking, consumption of coffee, tea and alcohol, and physical activity (Rasmussen et al, 2000; Husemoen et al, 2006). …”
Section: Introductionmentioning
confidence: 99%